Development of virtual tour media using local history to improve learning outcomes - Aminah Lubis; Ichwan Azhari; Samsidar Tanjung (Himpunan Pengembang Kurikulum Indonesia, 2025)
The research was motivated by the lack of student engagement and minimal visualization in local history learning, which has resulted in a limited understanding. Conventional media limitations have created epistemological and didactic obstacles that hinder effective learning. Therefore, a technology-based solution is needed to present historical objects interactively and contextually. This study aims to develop a 360° Virtual Tour learning media based on the local history of Candi Bahal to improve the learning outcomes of fourth-grade elementary school students in Social Studies. This study used a Research and Development (RnD) method with the 4D model (Define, Design, Develop, Disseminate). The research subjects included students and fourth-grade teachers at SD Negeri 0701 Rotan Sogo. Data were collected through observation, interviews, expert validation, and field trials. Results showed that the 360° Virtual Tour media was declared feasible by experts, practical for teachers and students, and effective in improving learning outcomes. The practicality scores reached 72.8 percent for students and 76.67 percent for teachers, while the n-Gain score was 0.56 (moderate category). The developed media contribute positively to making local history learning more contextual and engaging. Abstrak Latar belakang penelitian ini didasarkan pada rendahnya keterlibatan murid dan minimnya visualisasi dalam pembelajaran Sejarah lokal, yang menyebabkan pemahaman murid menjadi terbatas. Keterbatasan media konvensional menjadi hambatan epistimologis dan didaktik yang mengurangi efektivitas pembelajaran. Oleh karena itu, dibutuhkan solusi berbasis teknologi yang mampu menyajikan objek sejarah secara interaktif dan kontekstual. Penelitian ini bertujuan mengembangkan media pembelajaran Virtual Tour 360° berbasis sejarah lokal Candi Bahal untuk meningkatkan hasil belajar murid kelas IV SD dalam mata pelajaran IPS. Penelitian ini menggunakan metode Research and Development (RnD) dengan model 4D (Define, Design, Develop, Disseminate). Subjek penelitian terdiri dari murid dan guru kelas IV SD Negeri 0701 Rotan Sogo. Data dikumpulkan melalui observasi, wawancara, validasi ahli, dan uji coba lapangan. Hasil penelitian menunjukkan bahwa media Virtual Tour 360° dinyatakan layak oleh para ahli, praktis digunakan oleh guru dan murid, serta efektif dalam meningkatkan hasil belajar. Rata-rata skor kepraktisan oleh murid dan guru masing-masing mencapai 72,8 persen dan 76,67 persen, sedangkan skor efektivitas berdasarkan nilai n-Gain sebesar 0,56 (kategori sedang). Media ini memberikan kontribusi positif terhadap pembelajaran Sejarah lokal yang lebih kontekstual dan menarik. Kata Kunci: hasil belajar; pengembangan media; sejarah lokal; virtual tour